Study of Inequality in Providing Clean Water Access in Malang and Pandeglang Districts - Husna Yuni Wulansari; Tadzkia Nurshafira; Taradhinta Suryandari (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2018)
This paper seeks to analyse the disparity of clean water access fulfillment in Malang district and Pandeglang district. This issue is important due to two considerations. First, Indonesia’s National Medium-term Development Plan (RPJMN) 2015-2019 targets universal access to water and sanitation by 2019, yet it is still 71,14% fulfilled in 2016. Second, existing studies on this issue addressed the problem by using technical approach; limited finance and infrastructure, demographic and topographic condition. Such technical aspects are indeed important, however it tends to obscure political dimension, i.e. power relations and social structure dynamics that influence policies regarding access to water. Therefore, this paper will analyse the political dimension of the disparity in clean water access fulfillment. In analysing the problem, this paper will use discourse analysis (Laclau and Mouffe, 2001). This paper analyses the struggle among discourses in fixing the meaning of ‘access’ as a contested political arena. It will also identify the strategy of various actors in articulating their discourses through the establishment of a network of alliance that can accommodate different interests. This paper aims to be the basis of decision making process that considers and emancipates the difficult circumstances that society are facing and alternative discourse that they have.